Efecto de la apertura comercial en la producción agrícola en los países de América Latina, periodo 1988-2020 - Garrido Quizhpe, Gicela Raquel (2023)
Undoubtedly, Latin America is a region with a high concentration of primary activities, such as agriculture, given that, throughout history, it has not been able to emerge from this phase, which is why there is a vicious circle between agriculture and development. One solution to this problem is that trade liberalization will make it easier for them to increase their income and thus redistribute it in innovation that generates added value and, therefore, sustained development over time. According to data from the World Bank (2022), agriculture represents between 5 and 18% of per capita GDP in 20 Latin American countries. This research uses the econometric methodology of causality cointegration for Latin American countries, which are classified according to their income level, in the period 1998 - 2020. The results obtained show that there is a significant negative trend between agriculture and trade openness. However, there is a positive correlation between agriculture and the control variables: GDP per capita, gross fixed capital formation and taxes, at the same time it is determined that the variables present an order of integration of I (1), confirming that there is a strong cointegration and equilibrium in the short and long term. Likewise, there is bidirectional causality in all Latin American countries and unidirectional causality from agriculture to trade openness for PIMA and PIMB. Finally, it is recommended to create primary, export and extractivist innovation strategies, which privilege diversified, eco-efficient and value-added production, especially agricultural products, in order to allow farmers to improve their production and export their products to foreign markets.